O presente : algumas reflexões acerca das relações entre espelho, fotografia e espectador nos quadri specchianti de Michelangelo Pistoletto - Rocha, Raiara Kellem Cardoso (2018)
The 1960s were marked by major changes. Categorizations interspersed with the field of art were flexibilized and practices that allowed reconfiguring the role of the spectator in the works and artistic exhibitions were instituted. In this scenario of majo